PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN SEBAGAI VARIABEL MEDIASI PADA OFFICE COFFEE BANJARMASIN - Ramadhana, Fitri; Hidayati, Noor; Utomo, Setio (Bisnis Smart, 2020)
Fitri Ramadhana, D1A213069, 2018, Effect of Service Quality on Consumer Loyalty through Satisfaction as Mediation Variables in Office Coffee Consumers Banjarmasin. Guided by  Noor Hidayati and Setio Utomo. This study aims to determine the Effect of Service Quality (X) on Consumer Loyalty (Y) through Satisfaction (Z) as Mediation Variables in Office Coffee Banjarmasin. Respondents in this study amounted to 120 people who are Banjarmasin Office Coffee taken using accidental sampling techniques. Data collection techniques in this study were observation and questionnaires. Data analysis techniques using Path Analysis.The results of this study indicate that there is a direct positive and significant effect of Service Quality (X) on Consumer Loyalty (Y) produces a T statistics value of 2.920 with a probability of 0.004. There is a direct positive and significant effect on Service Quality (X) on satisfaction (Z) resulting in T statistics of 6.611 with a probability of 0.000. Satisfaction (Z) on Consumer Loyalty (Y) produces a T statistics value of 16.142 with a probability of 0.000.